Effects of Differences in Exercise Programs With Regular Resistance Training on Resting Blood Pressure in Hypertensive Adults: A Systematic Review and Meta-Analysis. Issue 1 (20th January 2023) - Igarashi, Yutaka
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Igarashi, Y. Effects of differences in exercise programs with regular resistance training on resting blood pressure in hypertensive adults: A systematic review and meta-analysis. J Strength Cond Res 37(1): 253–263, 2023—This systematic review and meta-analysis aimed to evaluate changes in resting blood pressure (RBP) with differences in regular resistance training (RT) programs. Inclusion criteria were randomized controlled trials involving hypertensive adults and interventions involving only RT of both the upper and lower limbs for ≥7 weeks. The weighted mean difference (WMD) was defined as the mean difference between the exercise and control groups, weighted by the inverse of the squared standard error for each study, and all WMDs in RBP were pooled as overall effects. A simple meta-regression analysis was performed to evaluate the relationship between RT variables (percentage 1 repetition maximum [1RM], number of repetitions, number of sets, and weekly frequency) and changes in RBP. Seventeen studies (646 subjects) were analyzed. The pooled WMDs in the resting systolic blood pressure (RSBP) and resting diastolic blood pressure (RDBP) decreased significantly but contained significant heterogeneity RSBP, −4.7 mm Hg (95% confidence interval [CI], −6.7 to −2.8; I 2 = 46.6%); RDBP, −3.5 mm Hg (95% CI, −4.9 to −2.1; I 2 = 39.1%). Meta-regression analysis revealed that an increase in % 1RM was significantly associated with a decrease in the RSBP (γ = −0.25x0 + 10.85, where γ represents the mean difference in RSBP, and x0 represents % 1RM [%]), and heterogeneity was alleviated ( I 2 = 0.0%). For reducing RSBP, regular RT with moderate or heavy loads may be more beneficial than regular RT with light loads.